دور الإدارة الإلكترونية في تحسين جودة الأداء الوظيفي لدى العاملين (Comprehensive Journal of Science, 2025)
This study aims to highlight the importance of e-management in enhancing the quality of employee performance. The study was conducted at the General Authority for the Care of Families of Martyrs, Missing Persons, and Amputees. Data was collected using a Likert scale questionnaire, which was distributed to 74 employees, and 52 questionnaires were returned. To answer the research questions, the Partial Least Squares (Smart-PLS) method was used. The results of the analysis indicate that e-management, specifically in terms of human resource efficiency and communication infrastructure, negatively affects the job performance of employees at the General Authority for the Care of Families of Martyrs, Missing Persons, and Amputees. مقدمــــة